"Social Work Is a Profession, Not an Ideology": A Qualitative Analysis of Student Perceptions of Social Justice Discussions in the Classroom. Issue 3 (27th May 2017) - Hansford, Candace; Ely, Gretchen E.; Flaherty, Chris; Meyer-Adams, Nancy
ABSTRACT: The purpose of this article is to describe student perceptions of their experiences around social justice discussions in the social work classroom through a qualitative, grounded theory framework. Student responses from a qualitative section of a survey were analyzed and sorted into three categories: perceived discrimination, heightened self-awareness/self-assessment, and future social work practice. Each of these categories was derived from comparable multiple themes stemming from the student responses. A conceptual model resulting from the analysis suggests that students who shared experiences of perceived discrimination during classroom discussions could develop an enhanced self-awareness, which would result in an added empathy for clients in their future social work practice. Suggestions for teaching strategies and directions for future research are also discussed.